2013
DOI: 10.1002/oby.20000
|View full text |Cite
|
Sign up to set email alerts
|

Serum adiponectin levels are associated with hepatitis B viral load in overweight to obese hepatitis B virus carriers

Abstract: Objective: This study aimed to investigate the association between serum adiponectin and chronic hepatitis B virus (HBV) infection. Design and Methods: We conducted a campus-based cross-sectional study in Northern Taiwan, an HBV-endemic country. A total of 506 participants, including 147 chronic HBV-infected individuals and 359 healthy controls, were assessed for anthropometric indices, serum adiponectin levels, serum HBV viral load and markers, serum alanine aminotransferase levels and metabolic factors. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
34
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 30 publications
2
34
0
Order By: Relevance
“…The participants’ average age ranged 33–61 years. Ten studies [3641, 4447] only reported MetS components in the form of continuous variables, and they mainly affected the pooled SMD of MetS components. Consequently, we did not consider in our analysis the MetS criteria they used.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The participants’ average age ranged 33–61 years. Ten studies [3641, 4447] only reported MetS components in the form of continuous variables, and they mainly affected the pooled SMD of MetS components. Consequently, we did not consider in our analysis the MetS criteria they used.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, we did not consider in our analysis the MetS criteria they used. In other words, whether these studies [3641, 4447] meet the MetS criteria (Q4: The MetS and its components were defined accurately) did not affect the statistical results (SMD), so they were labeled with “UR” (unrelated) for Q4 in Table 3. The remaining 20 studies [1017, 2635, 42, 43] reported ORs or crude data for calculating the ORs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4 ACKNOWLEDGEMENT The authors' declarations of personal and financial interests are unchanged from those in the original article. …”
mentioning
confidence: 99%